SWOT UEA SEBAGAI PUSAT PERDAGANGAN HALAL GLOBAL - Ariwiansyah, Furqon; Cahyani, Mutiara (Taksasila Edukasi Insani, 2024)
This study aims to analyze the potential, challenges, and strategies of the international halal market in the United Arab Emirates (UAE) using a SWOT analysis approach. Employing a descriptive-qualitative method and document analysis, the research identifies the UAE's strengths, such as its strategic location and government support, as well as weaknesses, including dependence on imports and a lack of harmonized halal standards. The significant opportunities in the global halal market and increasing consumer awareness of halal products present substantial growth potential. However, competition from other countries and geopolitical risks pose threats that require careful anticipation. The findings indicate that the UAE holds great potential to become a global halal market hub but requires comprehensive strategies. Strategic recommendations include diversifying the halal economy, fostering international collaboration to harmonize standards, and enhancing domestic production capacity. The study concludes that with the right strategies, the UAE can maintain its position as a leader in the global halal market and contribute to sustainable economic growth.Keywords : Halal market, United Arab Emirates, SWOT, descriptive-qualitative analysis, strategy, Islamic economics